Sensor de grafite/ácido polilático impresso em 3D para a determinação eletroquímica do explosivo 2,4,6-trinitrotolueno - Siqueira, Gilvana Pereira (2024)
Composite materials of graphite and polylactic acid (Gpt-PLA) produced in the laboratory were used to manufacture electrodes by additive manufacturing using the fused deposition modeling (FDM) technique for subsequent determination of the explosive 2,4,6-trinitrotoluene (TNT), considered a persistent organic pollutant, which can cause serious problems for human health, such as carcinogenic, hepatogenic and mutagenic effects, etc. The surface of the 3D printed material was characterized by scanning electron microscopy (SEM) and Raman spectroscopy, which revealed high roughness and the presence of defects in the graphite structure, which enhanced the electrochemical response of the TNT. Characterizations carried out by cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) indicated an excellent reversibility of the electrochemical process and a low value of charge transfer resistance (Rct) on the Gpt-PLA surface. The 3D printed Gpt-PLA electrode coupled to square wave voltammetry (SWV) showed adequate performance to quickly identify TNT species (around 7 s). Two reduction processes around -0.22 V and -0.36 V (vs. Ag|AgCl|KCl(sat.)) were selected for TNT detection, with linear ranges between 1.0 and 10.0 µmol L-1. Furthermore, detection limits of 0.52 and 0.66 µmol L-1 were achieved for both reduction steps. The proposed method was applied to determine TNT in different environmental water samples (tap water, river water and sea water) prepared in 0.01 mol L-1 HCl. Recovery values between 100 and 105% confirmed the accuracy of the analyses. Furthermore, adequate selectivity was achieved even in the presence of other explosives commonly used by military agencies, metal ions found in water and also some species capable of passivating the electrode. Such results indicate that the proposed device is promising for quantifying TNT residues in environmental samples, a viable strategy for on-site analysis.